THE DEGREE OF OBESITY OF ONE-HUMPED CAMELS DEPENDS ON THE SIZE OF THEIR HUMP - A.K. Tleumuratov; N.Y. Joldasov (Journals Park Publishing, 2022)
This article describes the age dynamics of one-humped camels and the production of meat in different types of pastures.
Keywords: Dromedar; tur; urchin